Effect of dynamic temperature stimulus to plantar surface of the foot in the standing position - Watanabe, Ryo; Kajimoto, Hiroyuki (Frontiers in Bioengineering and Biotechnology, 2016)
We have previously found that a vertical force or tactile sensation occurs when the temperature of a participant's skin changes rapidly. In this illusion, upward motion, pressure or force sensation is elicited when stimulus temperature rises rapidly, whereas in the opposite case, downward motion or pulling sensation is elicited. In this paper, we applied this phenomenon to the sole (plantar surface of the foot) to present the sensation of ground slope. To investigate this, we conducted an experiment that measured the correlation between stimulation temperature and front-back direction position of the center of gravity (COG). Participants stood on a thermal stimulator on Nintendo Wii Balance Board (WBB) and they remained standing during 30 s dynamic temperature stimulus. In result of analysis, it was suggested that dynamic thermal change in sole might influence standing position and the effect pattern was anomalous in case of the participants who reported a swaying sensation without a haptic sensation. This behavior might be applied to the diagnosis of the presence of thermoesthesia of the patients who might have disease with absence of thermoesthesia.